2013
DOI: 10.1021/ja407424v
|View full text |Cite
|
Sign up to set email alerts
|

Dangerous Liaisons between Detergents and Membrane Proteins. The Case of Mitochondrial Uncoupling Protein 2

Abstract: The extraction of membrane proteins from their native environment by detergents is central to their biophysical characterization. Recent studies have emphasized that detergents may perturb the structure locally and modify the dynamics of membrane proteins. However, it remains challenging to determine whether these perturbations are negligible or could be responsible for misfolded conformations, altering the protein's function. In this work, we propose an original strategy combining functional studies and molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
102
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(114 citation statements)
references
References 69 publications
11
102
0
1
Order By: Relevance
“…High‐resolution biophysical techniques commonly use detergent micelles to mimic a hydrophobic environment because they are easy to handle and very homogeneous in size. However, due to the artificial nature and frequent denaturing capabilities of detergents, as well as a high degree of curvature in micelles, membrane proteins and membrane‐associated peptides might not adapt their natural shape/topology, but might bend unnaturally under steric restraints 7, 30, 47. These structural artefacts can be avoided by using artificial vesicles named liposomes.…”
Section: Introductionmentioning
confidence: 99%
“…High‐resolution biophysical techniques commonly use detergent micelles to mimic a hydrophobic environment because they are easy to handle and very homogeneous in size. However, due to the artificial nature and frequent denaturing capabilities of detergents, as well as a high degree of curvature in micelles, membrane proteins and membrane‐associated peptides might not adapt their natural shape/topology, but might bend unnaturally under steric restraints 7, 30, 47. These structural artefacts can be avoided by using artificial vesicles named liposomes.…”
Section: Introductionmentioning
confidence: 99%
“…In one example, the solution structure of E. coli diacylglycerol kinase showed a domain-swapped trimer, whereas the same enzyme and two variants crystallized in a lipid bilayer showed no sign of domain swapping: the implication is such that the architecture and the catalytic properties of the active sites are different in both structures (43,44). In the other case, when the solution structure of the uncoupling protein UCP2 solubilized and purified in DPC was described (45), comparison with the high resolution x-ray structure of the bovine ATP/ ADP mitochondrial carrier crystallized in 3-lauramidopropyl-N,N-dimethylamine oxide micelles (46) suggested that it carried biases affecting biological interpretation (47). This raises the question of the behavior of a membrane protein once extracted from its native membrane environment and of the techniques to be used to explore this behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding UCP2, the physiological relevance of its solution structure was assessed with the help of theoretical calculations. Indeed, one major conclusion of this study was that combining functional and computational investigations is a promising general strategy that would be beneficial to analyze the structures of numerous membrane proteins (47). As a general guideline, alternative methods are required for structure validation, quality assessment, and enhancement (48).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, water permeability and lateral pressure profiles differ extensively in micelles and bilayers. As a result, MPs generally show a lower stability (Quick et al 2012) or cause the protein to adopt a non-physiological conformation (Zhou and Cross 2013b;Zoonens et al 2013). Because of these problems, much effort is being directed towards the development of new detergents with improved properties.…”
Section: Detergentsmentioning
confidence: 99%